Capital Market Development Over the Long Run: The Portfolios of UK Life Assurers Over Two Centuries - David Bogle; Christopher Coyle; John D. Turner (Queen's University Belfast, Queen's Management School, 2020)
What shapes and drives capital market development over the long run? In this paper, using the asset portfolios of UK life assurers, we examine the role of regulation, historical contingency and political reactions to events on the long-run development of the UK capital market. Government response to events such as war, hegemony-secured peace, and the wider macroeconomic environment was the ultimate determinant of major changes in asset allocation since 1800. Furthermore, when we compare the UK with the United States, we find that regulation played a limited role in shaping the asset portfolios of the UK life assurance industry.
Keywords: G11; G22; N20; N40; 330; Capital markets; asset management; life assurance; mutuals; mergers; regulation; United Kingdom; United States